NGHIÊN CỨU HÌNH THÁI, CẤU TRÚC CỦA MÀNG THỤ ĐỘNG Cr3+ TRÊN LỚP MẠ KẼM - Hương, Nguyễn Thị Thanh; Thắng, Lê Bá; Nam, Trương Thị; Chiến, Nguyễn Văn; Khương, Nguyễn Văn; Bảo, Lê Đức (Vietnam Journal of Science and Technology, 2015)
TÓM TẮT / ABSTRACT Research of morphology, microstructure of trivalent chrome conversion coating on zinc electroplating In this paper, the morphology, microstructure, thickness, weight and composition of the trivalent chrome conversion coating (CCCs) on zinc electroplating with different dipping times (10, 20, 40, 50, 60, 70 and 80 s) have been studied. The thickness, weight of the layer increases with dipping time in the bath. Thickness, weight of the CCCs as a function of dipping time. When the dipping time increases to 80